2019
DOI: 10.1128/aac.02016-18
|View full text |Cite
|
Sign up to set email alerts
|

Doravirine and the Potential for CYP3A-Mediated Drug-Drug Interactions

Abstract: Identifying and understanding potential drug-drug interactions (DDIs) are vital for the treatment of human immunodeficiency virus type 1 (HIV-1) infection. This article discusses DDIs between doravirine, a nonnucleoside reverse transcriptase inhibitor (NNRTI), and cytochrome P450 3A (CYP3A) substrates and drugs that modulate CYP3A activity. Consistent with previously published in vitro data and DDI trials with the CYP3A substrates midazolam and atorvastatin, doravirine did not have any meaningful impact on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 60 publications
5
31
0
Order By: Relevance
“…25 In vitro studies and clinical drug interaction studies indicated that CYP3A-mediated metabolism is a major contributor to the elimination of doravirine. 20,22,[26][27][28] Consistent with this finding, the majority of an absorbed oral dose of [ 14 C]-labeled doravirine in healthy subjects was recovered as oxidative metabolites. The oxidative metabolite M9 was the major metabolite of doravirine observed both in vitro in preparations from human liver and in vivo in human excreta and plasma.…”
supporting
confidence: 66%
See 4 more Smart Citations
“…25 In vitro studies and clinical drug interaction studies indicated that CYP3A-mediated metabolism is a major contributor to the elimination of doravirine. 20,22,[26][27][28] Consistent with this finding, the majority of an absorbed oral dose of [ 14 C]-labeled doravirine in healthy subjects was recovered as oxidative metabolites. The oxidative metabolite M9 was the major metabolite of doravirine observed both in vitro in preparations from human liver and in vivo in human excreta and plasma.…”
supporting
confidence: 66%
“…These results are consistent with previous clinical trials in which doravirine has not been shown to be a perpetrator of DDIs as a concomitant partner with other medications. [18][19][20][21] The trial was conducted with methadone administered at steady state and doravirine administered for 5 days. The 5-day duration was selected because, based on the half-life of doravirine, steady-state concentrations were expected to be attained within 5 days.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations